STRATEGI KEPEMIMPINAN DALAM PENGEMBANGAN KURIKULUM PAUD DI ERA TRANSFORMASI PENDIDIKAN - Nabilatuz Zakia, Dinda; Naura Sabrina, Dzakira; Nur Ramadhani, Mutia; Maya Kartika, Pasya; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze leadership strategies in developing Early Childhood Education (PAUD) curriculum in the era of educational transformation. Rapid changes in technology, social aspects, and student needs demand adaptive and innovative leadership in designing and developing curriculum. The method used in this study is a literature study by reviewing various sources in the form of scientific journals, books, and relevant research results. The results of the study indicate that effective leadership strategies in developing PAUD curriculum in the era of transformation include visionary thinking skills, collaboration with educators, utilization of technology in learning, and the ability to adapt to change. In addition, communicative and responsive leaders are able to create a flexible and child-centered learning environment. Thus, the right leadership strategy can improve the quality of PAUD curriculum to be more relevant to the demands of the times and able to optimize child development holistically. Keywords: Leadership 1, Curriculum 2, Transformation 3